Perubahan fungsi bandar kecil : pengalaman Tanjong Malim, Perak - Saleh Yazid, Rostam Katiman, Hussain Mohd Yusof (N/A, 2012)
Perubahan fungsi bandar kecil : pengalaman Tanjong Malim, Perak by Saleh Yazid, Rostam Katiman, Hussain Mohd Yusof,